Analisis Kepastian Hukum Bagi Pemilik Tanah Pasca Implementasi Pendaftaran Sertifikat Secara Elektronik - Sudarto Sudarto (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2022)
Electronic registration of land certificates has been implemented by the Government through the Kementerian Agraria dan Tata Ruang / Badan Pertanahan Nasional (ATR/BPN). However, certificate owners often doubt the legal force of electronic certificates, especially their validity to be used as evidence in court. This study examines specifically the juridical review regarding legal certainty obtained by the owner of an electronic land certificate. The research uses a normative juridical approach, with secondary data in the form of legal materials, primary, secondary and tertiary legal materials. Based on research, electronic certificates have a strong legal basis and have legal force as proof of rights to ownership and utilization of land. Thus, the owner of the certificate gets legal certainty in the form of protection of his land asset rights.